The Democratic Potential of Community-Based Initiatives - Visscher, Kors; Hurenkamp, Menno; Tonkens, Evelien (Politics of the Low Countries, 2025)
As governments in Western Europe have retreated from providing public services over the past decades, they have stimulated communities to take over many of these services. This has resulted in, among other things, a plethora of community-based initiatives (CBIs). CBIs are heralded by some for their innovative potential: they would address new problems. CBIs are also criticised for being undemocratic, as their activities can marginalise or overrule elected politicians and the citizens active in CBIs are not representative of the population. We argue that these different praises and criticisms implicitly depart from different democratic perspectives, specifically the representative and do-democratic perspectives. These different perspectives need to be explicated and compared in order to judge in what ways CBIs can and cannot be said to have democratic legitimacy, when assessed from different perspectives on democracy